Fat-lowering effects of isorhamnetin are via NHR-49-dependent pathway in Caenorhabditis elegans - Renalison Farias-Pereira (Current Research in Food Science, 2020)
Isorhamnetin (3-O-methylquercetin), a flavonol found in dill weed, sea buckthorn berries, kale and onions, has been suggested to have anti-obesity effects, but there is limited evidence of its mechanisms of action on lipid metabolism. The goal of this study was to investigate the effects of isorhamnetin on lipid metabolism using Caenorhabditis elegans as an animal model. Isorhamnetin reduced fat accumulation without affecting food intake or energy expenditure in C. elegans. The isorhamnetin's fat-lowering effects were dependent on nhr-49, a homolog of the human peroxisome proliferator-activated receptor alpha (PPARα). Isorhamnetin upregulated an enoyl-CoA hydratase (ech-1.1, involved in fatty acid β-oxidation) and adipose triglyceride lipase (atgl-1, involved in lipolysis) via NHR-49-dependent pathway at transcriptional levels. Isorhamnetin also upregulated the C. elegans AMP-activated protein kinase (AMPK) subunits homologs (aak-1 and aak-2), involved in energy homeostasis. These results suggest that isorhamnetin reduces body fat by increasing fat oxidation in part via NHR-49/PPARα-dependent pathway.